A case of cutaneous leiomyosarcoma - Kokcam, I.; Yilmaz, S.; Ozercan, R.; Yildirim, M.A. (My University, 1997)
Leiomyosarcomas of soft-tissue origin are extremely rare. A three centimetre sized tumor developed on the left lateral malleol of a 46-year- old woman. This tumor was diagnosed clinically as a malign melanoma but dermatopathological studies confirmed a leiomyosarcoma. The tumor was excised and the wound reconstructed with full-thickness skin graft. The literature was reviewed.
Bir kutanoz leiomyosarkoma olgusu
Keywords: Leiomyosarcoma